Managing companies with ukhuwwah approach as business core catalyst for sustainability - Mhd. Sarif, Suhaimi (Zes Rokman Resources, 2016)
There are many approaches to ensure businesses are capable of sustaining good performance. Strategic bond or ukhuwwah enables managers, employees and key stakeholders to work in collaborative and cooperative manner in formulating, implementing and evaluating strategies for sustainable competitive advantage and performance. The use of ukhuwwah approach as core catalyst in managing companies enhances capability and capacity building of companies. Ukhuwwah is developed under several stages, namely get knowing (ta’aruf), get understanding (tafahum), give mutual help (ta’awun), mutual protection (takaful), and mutual love and care (tanasur). This study argues that ukhuwwah approach is not only serves as enabler and catalyst for the business survival and growth, but also serves as core catalyst for business to enjoy sustainability. Ukhuwwah approach provides universal and high contextual environment. The interactions with many stakeholders enable rich and useful information, which is useful for forecasting unit of many organizations. A personal interview five small and medium companies found out that ukhuwwah enables core competencies to be acquired, transferred, stored and improved. However, the results are contextual specific to the five firms being interviewed.